If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (3x + -5) + (-7x + 3) = 0 Reorder the terms: (-5 + 3x) + (-7x + 3) = 0 Remove parenthesis around (-5 + 3x) -5 + 3x + (-7x + 3) = 0 Reorder the terms: -5 + 3x + (3 + -7x) = 0 Remove parenthesis around (3 + -7x) -5 + 3x + 3 + -7x = 0 Reorder the terms: -5 + 3 + 3x + -7x = 0 Combine like terms: -5 + 3 = -2 -2 + 3x + -7x = 0 Combine like terms: 3x + -7x = -4x -2 + -4x = 0 Solving -2 + -4x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '2' to each side of the equation. -2 + 2 + -4x = 0 + 2 Combine like terms: -2 + 2 = 0 0 + -4x = 0 + 2 -4x = 0 + 2 Combine like terms: 0 + 2 = 2 -4x = 2 Divide each side by '-4'. x = -0.5 Simplifying x = -0.5
| ln(x+1)+ln(x+4)=ln(x+9) | | -2(5x+4)=-27x-18-7 | | 3x+6+x-11+x-10=360 | | 3.2d=15.75-54.15 | | 3x+4(x+6)=410 | | 6+7x=4x+18 | | 2x+27=6x+3 | | .5x+3y=2 | | .67=ln(y) | | h=16t^2+vt+s | | 12+(5-9)= | | 3.2d=15.75+54.15 | | 7-x=7x+39 | | 6x+2x-9=95 | | -5x-2=x-2 | | 20x+35x=121 | | 5-2(x+2)=13 | | 14x-3+30=16x+11 | | x/3*4=20 | | 95=8x-8 | | 5+2(3x-8)=2x+9 | | 11+d+(-4)ford=-6 | | k^2-32k+8=0 | | 3(8.2-x)=6.6 | | -2(3x-2)=4-6x | | 26=6(5-a)+2 | | 7*5=63-N | | x/34=20 | | 56=t-25 | | 12x+11+69=25x+2 | | -5x-4=-3x+10 | | -10p-8=2 |